Pelatihan Penggunaan Media Sosial Menuju Perbaikan Ekonomi Di Era Digitalisasi Bagi Ibu-Ibu Aisyiyah Ranting Kampung Kebon Sawangan Depok - Ujang Syaifudin Sumaji; Adi Supriadi; Muhammad Arif Adriyanto (Abdimisi, 2022)
Aisyiyah recitation mothers in the Cinangka subdistrict, Depok city, have not been able to take advantage of their social media so that it can be economically valuable. So far, mothers only use cellphones to communicate with friends and family without economic value. This is due to the lack of understanding about the proper use of cellphones which can have economic value. The community service entitled "Using Social Media Towards Economic Improvement in the Era of Digitalization for Aisyiyah Mothers in Kampung Kebon Kelurahan Cinangka Sawangan Depok" aims to provide knowledge about sales through social media and invite and instill awareness in Aisyiyah mothers that it is very important to develop marketing through social media to increase the added value of the family economy. The target of this dedication is all Management and members of PR. Aisyiyah and those in the Cinangka sub-district, Sawangan sub-district, Depok city. The results of this PKM proved that Aisyiyah's mothers could master how to sell through e-commerce so that they could still increase the added value of the family's economy.